Analisis Highest and Best Use atas Aset Tetap Milik Pemerintah Kota Batam - Farhan Ramadhani Santoso; Nurbiyanto Nurbiyanto (Universitas Batanghari Jambi, 2021)
This study discusses and implements the Highest and Best Use (HBU) analysis method for a fixed asset that is under the management and ownership of the Batam City Government in the form of land and buildings that are not utilized at the Jodoh Traditional Main Market which is located on Jalan Duyung, Lubuk Baja District, Batam City. The HBU analysis in this study assumes the object as though vacant and analyzes four aspects which include legal aspects, physical aspects, financial aspects, and maximum productivity. The development alternative that is able to produce the highest increase in land value on the land, then the development alternative is chosen as an alternative development that has the highest level of optimization. According to HBU's analysis, the most profitable alternative for land development is as a commercial property with mixed use types including traditional markets, shop houses/ruko, and convenience stores/food courts with an increase in land value of 1.342% or to Rp. 20,248,791.32.-/m2.